Understanding the impact of hydrodynamics on coastal erosion in Latin America: a systematic review - Vallarino Castillo, Ruby; Negro Valdecantos, Vicente; del Campo, José María (Frontiers in Environmental Science, 2023)
The coastal areas of Latin America are home to a significant proportion of the regional population and face diverse challenges related to natural dynamics and climate change. One of the most significant challenges is coastal erosion, especially shoreline retreat and loss of natural defense systems in coastal zones. Coastal erosion, resulting from hydrodynamic processes such as wave action, tides, and currents, combined with sea-level rise, further exposes densely populated areas to risks. The mechanisms responsible for erosion in sandy beaches are varied and sometimes interact synergistically, generating short-term erosive processes. Consequently, this paper research presents a systematic review encompassing multiple case studies in Mexico, Central America, and South America, identifying six categories of interdependent factors that influence coastal erosion: oceanic-climatic, atmospheric-climatic, anthropogenic, geomorphological and bathymetric, geological and tectonic, and climate change-related factors. These factors are analyzed individually, highlighting their specific effects in different countries of Latin America. Additionally, methods, tools and data sources used by researchers in the region to study short and long-term changes in coastal erosion are examined. These methods, tools and data sources were classified into six clusters indicating their association, frequency, and application. These are related to cartographic data, fieldwork, modeling of hydrodynamic processes, analysis of shoreline change, aerial and satellite imagery, and marine and atmospheric condition data. Finally, the future research challenges in coastal erosion in the region are emphasized, highlighting the importance of international cooperation to enhance knowledge transfer and develop strategies and management plans that mitigate the risks faced by populations in coastal areas.